Macronutrient Intake and Obesity In Adolescents: A Meta-Analysis Study - Ainun, Nur; Simbolon, Demsa (Universitas Airlangga, 2024)
Obesity is a condition with excess body fat due to an imbalance in energy intake consumed more than the physical activity expended. Adolescents who are obese can increase the risk of degenerative diseases. This study aimed to determine the relationship between macronutrients, including carbohydrate, protein, and fat intake, and obesity in adolescents. This study uses a meta-analysis method. Articles were taken from Google Scholar, PubMed, and Science Direct databases. The articles analyzed were articles published from 2000 – 2022, full text; the keywords used for the search were